The Alpha‐defensin Test for Periprosthetic Joint Infection Outperforms the Leukocyte Esterase Test Strip. Issue 1 (January 2015) - Deirmengian, Carl; Kardos, Keith; Kilmartin, Patrick; Cameron, Alexander; Schiller, Kevin; Booth, Robert E.; Parvizi, Javad
Abstract: Background: Synovial fluid biomarkers have demonstrated diagnostic accuracy surpassing the currently used diagnostic tests for periprosthetic joint infection (PJI). Questions/purposes: The purpose of this study is to directly compare the sensitivity and specificity of the synovial fluid α‐defensin immunoassay to the leukocyte esterase (LE) colorimetric test strip. Methods: Synovial fluid was collected from 46 patients meeting the inclusion criteria of this prospective diagnostic study. Synovial fluid samples were tested with both a novel synovial‐fluid‐optimized immunoassay for α‐defensin and the LE colorimetric test strip. The Musculoskeletal Infection Society (MSIS) definition was used to classify 23 periprosthetic infections and 23 aseptic failures; this classification was used as the standard against which the two diagnostic tests were compared. Results: The synovial fluid α‐defensin immunoassay correctly predicted the MSIS classification of all patients in the study, demonstrating a sensitivity and specificity of 100% for the diagnosis of PJI. The α‐defensin assay could be read for all samples, including those with blood in the synovial fluid. The leukocyte esterase test strip could not be interpreted in eight of 46 samples (17%) as a result of blood interference. Analysis of the LE strips that could be interpreted yielded a sensitivity of 69% and a specificity of 100%. Conclusions: The synovial fluid α‐defensin immunoassay outperformed the LE colorimetric test strip in this study and provided reliable results even when the LE test strip failed as a result of blood interference. The simple analytic results provided by the α‐defensin immunoassay, compared with the more complex and interpretive nature of both the MSIS criteria and LE colorimetric test strip, make it a highly attractive diagnostic tool. Level of Evidence: Level II, diagnostic study. See Guidelines for Authors for a complete description of levels of evidence.